A Rare Case of Giant Congenital Melanocytic Nevi: A Case Report - Marina Saribulan; Ennesta Asri (HM Publisher, 2023)
Background: Giant congenital melanocytic nevi are often characterised as melanocytic lesions present at birth. It is thought that it affects 1 in 20,000 births. The lesion is significant because it may be associated with serious consequences, such as malignant melanoma, and may also result in neurological deficits, such as neurocutaneous melanocytosis. This study aimed to present the case of giant congenital melanocytic nevus as a rare case. Case presentation: This study reported a 14-year-old female reported with large blackish rough spots on the trunk that were neither itchy or painful since birth. The patient had no previous history of convulsions, headaches, or vomiting. Plaque hyperpigmentation, macula hyperpigmentation, and hypertrichosis were found on the trunk. Dermoscopy show reveals brown-black homogeneity. Histopathology examination reveals brown-pigmented nevus cells distributed diffusely, with some nevus cells surrounding adnexa skin. Conclusion: Regular examination is essential to monitor the possibility of neurocutaneous melanosis and malignant melanoma development.